The fading guardian: clinical relevance of TP53 null mutation in high-grade serous ovarian cancers - Biatta, Chiara M.; Paudice, Michele; Greppi, Marco; Parrella, Veronica; Parodi, Alessia; De Luca, Giuseppa; Cerruti, Gianna Maria; Mammoliti, Serafina; Caroti, Cinzia; Menichini, Paola; Fronza, Gilberto; Pesce, Silvia; et al. (Frontiers in Immunology, 2023)
Background: we evaluated the concordance between immunohistochemical p53 staining and TP53 mutations in a series of HGSOC. Moreover, we searched for prognostic differences between p53 overexpression and null expression groups.Methods: patients affected by HGSOC were included. For each case p53 immunohistochemical staining and molecular assay (Sanger sequencing) were performed. Kaplan-Meier survival analyses were undertaken to determine whether the type of TP53 mutation, or p53 staining pattern influenced overall survival (OS) and progression free survival (PFS). This is a provisional file, not the final typeset article Results: 34 HGSOC were considered. All cases with a null immunohistochemical p53 expression (n=16) showed TP53 mutations (n=9 nonsense, n=4 in-frame deletion, n=2 splice, n=1 in-frame insertion). 16 out of 18 cases with p53 overexpression showed TP53 missense mutation. Follow up data were available for 33 out of 34 cases (median follow up time 15 month). We observed a significant reduction of OS in p53 null group [HR = 3.64,].Conclusion: immunohistochemical assay is a reliable surrogate for TP53 mutations in most cases. Despite the small cohort and the limited median follow up, we can infer that HGSOC harboring p53 null mutations are a more aggressive subgroup.